Diffusion and Swelling Measurements in Pharmaceutical Powder Compacts Using Terahertz Pulsed Imaging. Issue 5 (2nd February 2015) - Yassin, Samy; Su, Ke; Lin, Hungyen; Gladden, Lynn F.; Zeitler, J. Axel
<x xml:space="preserve">Abstract</x> Tablet dissolution is strongly affected by swelling and solvent penetration into its matrix. A terahertz‐pulsed imaging (TPI) technique, in reflection mode, is introduced as a new tool to measure one‐dimensional swelling and solvent ingress in flat‐faced pharmaceutical compacts exposed to dissolution medium from one face of the tablet. The technique was demonstrated on three tableting excipients: hydroxypropylmethyl cellulose (HPMC), Eudragit RSPO, and lactose. Upon contact with water, HPMC initially shrinks to up to 13% of its original thickness before undergoing expansion. HPMC and lactose were shown to expand to up to 20% and 47% of their original size in 24 h and 13 min, respectively, whereas Eudragit does not undergo dimensional change. The TPI technique was used to measure the ingress of water into HPMC tablets over a period of 24 h and it was observed that water penetrates into the tablet by anomalous diffusion. X‐ray microtomography was used to measure tablet porosity alongside helium pycnometry and was linked to the results obtained by TPI. Our results highlight a new application area of TPI in the pharmaceutical sciences that could be of interest in the development and quality testing of advanced drug delivery systems as well as immediate release formulations. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1658–1667, 2015